Cognitive Remediation and Social Recovery in Early Psychosis (CReSt-R): protocol for a pilot randomised controlled study - E. Frawley; M. Cowman; M. Cella; D. Cohen; E. Ryan; B. Hallahan; C. Bowie; C. McDonald; D. Fowler; T. Wykes; G. Donohoe (Pilot and Feasibility Studies, 2022)
Abstract Background Psychosis, even in its early stages, is associated with significant disability, causing it to be ranked ahead of paraplegia and blindness in those aged 18–35 in terms of years lived with disability. Current pharmacological and psychological interventions intervention have focused primarily on the reduction of positive symptoms (hallucinations and delusions), with little benefit to domains of psychosis such as cognitive difficulties and social and occupational functioning. Methods/design The CReSt-R intervention trial is a single center, pilot randomised controlled study based at the National University of Ireland (NUI), Galway. The trial will recruit participants from four clinical sites with assessment and intervention completed by the primary NUI Galway team. The trial will explore the feasibility, acceptability, and effectiveness of a novel psychosocial intervention for early psychosis based on a combined cognitive remediation training and cognitive behavioural therapy approach focused on social recovery. Participants, aged 16–35 within the first 5 years of a diagnosed psychotic disorder, will be recruited from the Children and Adolescent Mental Health Service and the Adult Mental Health Services in the region. Discussion Cognitive remediation training (for improving cognition) and social recovery focused cognitive behavioural therapy, have both separately demonstrated effectiveness. This trial will evaluate the feasibility, acceptability, and explore the efficacy of a treatment approach that combines both approaches as part of an integrated, multicomponent intervention. Trial registration Cognitive Remediation & Social Recovery in Early Psychosis (CReSt-R): ClincialTrials.gov Identifier NCT04273685. Trial registered Feb 18th, 2020. Last updated April 14th, 2021.